1971
DOI: 10.1136/jnnp.34.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of thoracic intervertebral disc protrusions

Abstract: SUMMARY A series of 14 patients with a protruded thoracic intervertebral disc is reported. We believe that the true incidence may be as high as one patient per million population per annum. Trauma, sometimes mild, seems to have played a significant role in this series. This fact coupled withpronounced numbnessand disagreeableparaesthesiae should suggest the diagnosis with thoracic spinal lesions. Armed with clinical suspicion, radiological verification of the lesion can be expected using a thorough myelographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
1
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(77 citation statements)
references
References 18 publications
1
72
1
2
Order By: Relevance
“…All of the patients in this series deteriorated following laminectomy. More satisfactory results have been reported with the posterolateral approach (Capener, 1954;Hulme, 1960;Chesterman, 1964;Carson, Gumpert and Jefferson, 1971;Jefferson, 1975).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…All of the patients in this series deteriorated following laminectomy. More satisfactory results have been reported with the posterolateral approach (Capener, 1954;Hulme, 1960;Chesterman, 1964;Carson, Gumpert and Jefferson, 1971;Jefferson, 1975).…”
Section: Discussionmentioning
confidence: 91%
“…Key in 1838 is reported to have described cord injury secondary to thoracic intervertebral disc protrusion in an autopsy specimen (Carson, Gumpert and Jefferson, 1971). Several authors since that time have documented cases of cord injury resulting from thoracic disc prolapse (Middleton and Teacher, 19II;Mixter and Barr, 1934;Hawk, 1936;Haley and Perry, 1950;Logue, 1952;Love and Schorn, 1965).…”
mentioning
confidence: 99%
“…In contrast, symptomatic forms are rare. Carson et al [10] estimated the annual incidence of symptomatic thoracic herniated discs to be one case in a million. Other authors have reported less than 0.5% of surgical procedures for herniated discs involving a thoracic disc [2,20].…”
Section: Introductionmentioning
confidence: 99%
“…4 Arce and Dhormann 5 reported that 75% of cases occurred below T8, whereas 3% of cases occurred between T1 and T2, and less than 1% occurred between T2 and T3. Disk degeneration is the main causing factor.…”
mentioning
confidence: 99%